Surgical outcomes and prognostic factors of non-metastatic radiation-induced sarcoma of bone. Issue 2 (February 2020) - Tsuda, Yusuke; Lowe, Martin; Evans, Scott; Parry, Michael C.; Stevenson, Jonathan D.; Fujiwara, Tomohiro; Kaneuchi, Yoichi; Le Nail, Louis-Romee; Jeys, Lee M.
Abstract: Background: The survival and prognostic factors in non-metastatic, radiation-induced bone sarcomas of bone have not been described. Moreover, the quantitative data about surgical outcomes and complications after limb-salvage surgery versus amputation are quite limited. Methods: Twenty-five patients with non-metastatic, radiation-induced sarcoma of bone who underwent definitive surgery were analysed. Histological diagnosis was osteosarcoma in 19 and undifferentiated pleomorphic sarcoma in six. The definitive surgery was limb-salvage surgery in 15 patients and an amputation in 10. Results: The 5-year overall survival rate (OS) and the 5-year event-free survival rate (EFS) were 53% (95% CI 31%–70%) and 40% (21%–59%), respectively. Patients with wide or radical surgical margins (n = 13) showed significantly better OS compared with those with marginal (n = 8) or intralesional (n = 2) margins (5-year OS, radical or wide = 74%, marginal = 17%, intralesional = 0%, p = 0.044). The risk of local recurrence was significantly higher in the limb-salvage group compared to the amputation group (49% vs 0%, p = 0.011). OS and EFS were not significantly different between limb-salvage group and an amputation group (p = 0.188 and 0.912, respectively). Conclusions: We believe non-metastatic, radiation-induced sarcoma of bone should be resected with the aim of achieving wide or radical margins. Although limb-salvage surgery was related to higher rates of local recurrence compared with those of the amputation group, OS and EFS were not different among two groups. Surgeons need to discuss the higher risk of local recurrence in limb-salvage surgery.